A Comparative Analysis of Regional Inequality: the Case of Romania and Poland: Array - Cojocaru (Diaconescu), Oana Mirela (Journal of Danubian Studies and Research, 2020)
There is a major interest from international and national bodies, but also from researchers for measuring inequality, materialized in numerous reports, studies and researches in the field. Multiple indicators are used to generate data and analyse the dynamics and patterns of inequality in order to find solutions to reduce economic disparities. This paper intends to carry out a comparative analysis regarding regional inequality. In order to carry out this analysis we have chosen two countries, Romania and Poland. We have analysed regional inequality based on regional Gross Domestic Product (GDP), for the period 2007-2016, and also based on the structural funds for 2007-2013. For measuring inequalities, we have used Theil index. Our results emphasize that there are significant inequalities between the regions of the two analysed countries and also that there is greater inequality in Romania than in Poland. The results of the study should be of interest to the policy makers as measuring and reducing inequality is a necessary process for meeting the objective of reducing European regional disparities and ensuring sustainable economic growth.